Mastering microsoft windows vista home : - Hart-Davis, Guy (Wiley Pub., 2007)
Configure, run, and troubleshoot Windows Vista Home Premium or Windows Vista Home Basic with the detailed coverage you’ll find in this comprehensive guide. With a task-based approach and clear instructions, this book helps you become an advanced user of Windows Vista—even if you’re just starting out. From administering your computer and surfing the Web securely to advanced maneuvers such as creating your own movies and burning DVDs, you’ll find what you need to master the powerful features of Windows Vista.